Effect of Formononetin on Lipopolysaccharide-Induced Depressive-Like Behaviors and Neuroinflammation in Mice - Li, Mengyuan; Liu, Hui; Peng, Shuaijun; Su, Pan; Xu, Erping; Bai, Ming; Li, Yucheng (Chinese medicine and natural products, 2023)
Objective The objective of this article is to explore the effect of formononetin (FMN) on depressive-like behaviors and neuroinflammation in lipopolysaccharide (LPS)-induced mice.Methods After acclimatization, male Institute of Cancer Research mice were randomly divided into normal group, LPS group, paroxetine group (20 mg/kg), FMN low-dose group (20 mg/kg, FMN20), and FMN high-dose group (40 mg/kg, FMN40), with eight mice in each group. The depressive-like behaviors were observed by sucrose preference test, tail suspension test (TST), and open field test. The protein and mRNA levels of interleukin-6 (IL-6), interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α) in the hippocampus were determined by enzyme-linked immunosorbent assay and real-time quantitative polymerase chain reaction. The expression level of ionized calcium-binding adapter molecule 1 (Iba-1) in the hippocampus was observed by immunofluorescence staining to evaluate the activation level of microglia.Results Compared with the control group, the sucrose preference rate, the activity time of the central area, the distance of the central area, and the number of times of entering the central area were significantly decreased in the LPS group (p < 0.01), and the immobility time of TST was significantly prolonged (p < 0.05), the expression levels of IL-6, IL-1β, and TNF-α protein and mRNA in hippocampus were significantly increased (p < 0.01), and the fluorescence intensity of Iba-1 in CA1, CA3, and DG regions of hippocampus was significantly increased (p < 0.01). Compared with the LPS group, the sucrose preference rate, central area activity time, central area activity distance, and the number of times of entering the central area were significantly increased (p < 0.05 or p <0.01) in the FMN group, and TST immobility time was significantly shortened (p < 0.01), the expression levels of IL-6, IL-1β, and TNF-α protein and mRNA in the hippocampus were significantly decreased (p < 0.05 or p < 0.01), and the fluorescence intensity of Iba-1 in CA1, CA3, and DG regions of hippocampus was significantly decreased (p < 0.01).Conclusion FMN could inhibit LPS-induced activation of microglia, reduce hippocampal neuroinflammation, and improve depressive-like behaviors in mice.
Keywords: formononetin; depression; LPS; neuroinflammation; proinflammatory cytokines; activation of microglia